Shrews Under-Represented in Fruit Farms and Homesteads - Linas Balčiauskas; Vitalijus Stirkė; Andrius Garbaras; Laima Balčiauskienė (Animals, 2023)
Shrews are a less studied group of small mammals than rodents. Between 2018 and 2022, we surveyed 23 sites in Lithuania, including natural and anthropogenic habitats, with the aim to assess the proportion of Soricidae in small mammal communities and their diet based on stable isotope analysis. The average representation of Soricidae was 3.1%, about half the long-term average in other habitats in the country. The highest proportions were in meadows and farmsteads, at 4.9% and 5.0% respectively. Shrews were not trapped on farms or in young orchards, and their relative abundance was very low in intensively managed orchards (0.006 individuals per 100 trap days). Neomys fodiens and N. anomalus were unexpectedly found in homesteads, including in outbuildings. Sorex araneus and S. minutus had similar diets. The trophic carbon/nitrogen discrimination factor between invertebrates and shrew hair was 2.74‰/3.98‰ for S. araneus, 1.90‰/3.78‰ for S. minutus in the orchards. The diet of N. fodiens and N. anomalus at the homesteads requires further investigation. We propose that the under-abundance of shrews may be due to contamination by plant protection products and a lack of invertebrates under intensive agricultural practices.